2008
DOI: 10.1021/ic702405d
|View full text |Cite
|
Sign up to set email alerts
|

Sarcoplasmic Reticulum Calcium ATPase Is Inhibited by Organic Vanadium Coordination Compounds: Pyridine-2,6-dicarboxylatodioxovanadium(V), BMOV, and an Amavadine Analogue

Abstract: The general affinity of the sarcoplasmic reticulum (SR) Ca 2+ -ATPase was examined for three different classes of vanadium coordination complexes including a vanadium(V) compound, pyridine-2,6-dicarboxylatodioxovanadium(V) (PDC-V(V)), and two vanadium(IV) compounds, bis(maltolato)oxovanadium(IV) (BMOV), and an analogue of amavadine, bis(N-hydroxylamidoiminodiacetato)vanadium(IV) (HAIDA-V(IV)). The ability of vanadate to act either as a phosphate analogue or as a transition-state analogue with enzymes' catalysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
59
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 51 publications
(62 citation statements)
references
References 56 publications
3
59
0
Order By: Relevance
“…15,16 The broadening of NMR vanadate signals upon interaction with proteins has also been previously reported for several vanadate complexes. [17][18][19][20] As observed by SDS-PAGE gel electrophoresis, the isolation of actin, according to Pardee and Spudich, 21 produced a G-actin (42.3 kDa) with 99% purity (not shown), which allows concluding that the NMR observations described above are due to the interaction of the monomeric state of actin, G-actin, with decavanadate. On the other hand, the addition of actin in its polymerized form, F-actin, up to 50 mM, induces a much smaller broadening of V 10 signals (1.5-fold), in comparison with G-actin, suggesting that decavanadate protein binding sites are encrusted upon actin polymerization.…”
Section: Introductionmentioning
confidence: 75%
See 2 more Smart Citations
“…15,16 The broadening of NMR vanadate signals upon interaction with proteins has also been previously reported for several vanadate complexes. [17][18][19][20] As observed by SDS-PAGE gel electrophoresis, the isolation of actin, according to Pardee and Spudich, 21 produced a G-actin (42.3 kDa) with 99% purity (not shown), which allows concluding that the NMR observations described above are due to the interaction of the monomeric state of actin, G-actin, with decavanadate. On the other hand, the addition of actin in its polymerized form, F-actin, up to 50 mM, induces a much smaller broadening of V 10 signals (1.5-fold), in comparison with G-actin, suggesting that decavanadate protein binding sites are encrusted upon actin polymerization.…”
Section: Introductionmentioning
confidence: 75%
“…Taken together, the presence of ATP promotes the broadening of monomeric NMR vanadate signal but it prevents the broadening of decavanadate signals, suggesting that this nucleotide promotes monomeric vanadate interaction with actin but on contrary blocks decavanadate interaction. 15 The broadening of 20) and has served on the Editorial Boards of scientific journals. To date, he has supervised and/or co-supervised more than 80 post-doc, PhD, MSc and undergraduate students, and has published about 60 peer-reviewed journal articles, reviews and book chapters.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mitochondria, for instance, a potential producer of reactive oxygen species, has been recently suggested to be a potential target of decavanadate [17], being suggested that mitochondrial membrane depolarization is a key event in vanadate-induced necrotic cell death of cardiomyocytes [18]. Studies have been done to learn more about the contribution of decameric vanadate species and also about the same vanadium complexes used in the present study, on Ca 2+ -ATPase from sarcoplasmatic reticulum, a transmembrane transport system that is involved in the regulation of muscle contraction [19]. Also, in skeletal muscle cells, it has been demonstrated that decameric vanadate also modulate myosin and actomyosin ATPase activities, responsible for the energy transduction that occurs during the process of muscle contraction [20,21].…”
Section: Introductionmentioning
confidence: 89%
“…8 SR Ca 2+ -ATPase activity is also inhibited by vanadium complexes such as vanadium-citrate and bis(maltolato)oxovanadium(IV) (BMOV) ( Table 1). 47,48 These and other vanadium compounds have been described in the treatment of diabetes mellitus. 49 Furthermore, decavanadate, 50 and compounds containing decavanadate 51 have been reported to lower glycemic levels, 50,51 and to normalize plasma lipid profiles.…”
Section: Ca 2+ -Atpase Inhibitorsmentioning
confidence: 99%